O rap e suas ressignificações - Teodósio, Marcela Dias (Universidade Federal de São Carlos, 2011)
z This study aims to analyze the linguistic practices by hip hop young activists, specially, through the artistic expression of the rap, conceived as the most expressive face of the movement, where the young people use a specific language to referring to the problems related to the daily routine of the suburbs. Among them, may be cited, violence, the poverty, unemployment and the failures in the government. To accomplish the proposed research, the main themes presented in the rap lyrics were selected, and, later, the semantic fields concerning the same themes, composed from the following lexical units, mother, suburbs, slums, ghettos, politics, hip hop and school were elaborated. From the elaboration of these semantic fields, it was possible to observe how such units are described in accordance with three dictionaries from different typologies, O Mini Houaiss Dicionário de Língua Portuguesa, o Dicionário Aurélio e o Dicionário de Usos do Português, in comparison with the meanings proposes in the rap lyrics, to verify the maintenance occurrence or removal, according to the relation of the sense of the words.
Keywords: Linguística; Língua portuguesa - estudo e ensino; Dicionários; Música; Rap; Language use; Dictionaries; LINGUISTICA, LETRAS E ARTES::LINGUISTICA